Efecto del contenido de sílice amorfa en la ceniza de la cáscara de arroz sobre la resistencia a la compresión en morteros de cemento portland y porosidad y absorción en concretos de cemento portland. - Avalos Esquivel, Grover Angelo (2012)
The high energy consumption and pollution involved collateral cement manufacturing, has been a concern to start looking for materials that partially replace cement and reduce the environmental cost of manufacture. The use of rice husk ash (CCA) as pozzolanic addition, it helps reduce the environmental impact caused by the production of cement, to the extent that allows partial replacement of the latter in cementitious materials.